2017
DOI: 10.1002/jpen.1042
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Adult Inpatients With Malnutrition

Abstract: Malnutrition is underrecognized by physicians. However, further research is needed to determine if physician recognition and treatment of malnutrition can improve outcomes. The most important criteria for identifying malnourished patients in our cohort were weight loss and reduced energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Based on the degree of the reduction in energy intake, weight loss, muscle loss, fat loss or fluid accumulation, we classified malnutrition as moderate or severe as described by White et al (27) . Vest et al (3) further describe the methods used at Christiana Care to identify malnutrition.…”
Section: Identification Of Malnutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the degree of the reduction in energy intake, weight loss, muscle loss, fat loss or fluid accumulation, we classified malnutrition as moderate or severe as described by White et al (27) . Vest et al (3) further describe the methods used at Christiana Care to identify malnutrition.…”
Section: Identification Of Malnutritionmentioning
confidence: 99%
“…Malnutrition can be caused by starvation, chronic disease-related inflammation and acute disease-related inflammation (2) . The prevalence of malnutrition varies widely among hospitalised adults, with estimates ranging from 4% to 45% (3)(4)(5)(6)(7)(8) . Multiple studies report adverse effects of malnutrition, which include a prolonged length of stay (5)(6)(7) , increased overall and in-hospital mortality (5)(6)(7) , increased risk of readmission (6,7,9,10) and higher hospitalisation costs (6,10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Within the US, malnutrition still goes unrecognized by the clinicians and is associated with longer hospital length of stay and higher morbidity, mortality, and healthcare costs. 5,6 Health-related quality of life (HRQOL) assesses patients' physical, psychological, social, and emotional functioning from their own experience and perspective, therefore identifying individuals who might benefit from clinical interventions. [7][8][9] Prospective studies among HNC patients have shown an association between nutrition status and HRQOL outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment‐related side effects such as dry mouth, decreased appetite, and difficulties with chewing and swallowing compromise oral intake, leading to significant weight loss and malnutrition 2‐4 . Within the US, malnutrition still goes unrecognized by the clinicians and is associated with longer hospital length of stay and higher morbidity, mortality, and healthcare costs 5,6 …”
Section: Introductionmentioning
confidence: 99%